2002
DOI: 10.1351/pac200274081339
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloid synthesis via [3+2] cycloadditions

Abstract: Tin-lithium exchange on (2-azaallyl)stannanes affords nonstabilized 2-azaallyllithiums (2-azaallyl anions) that undergo [π4s+π2s] cycloadditions with alkenes to afford pyrrolidines. The scope of this method has been expanded to include 2-azapentadienyllithiums and heteroatom-substituted 2-azaallyllithiums. Alternatively, the (2-azaallyl)stannanes may also be used to generate nonstabilized azomethine ylides via N-alkylation/destannylation or N-protonation/destannylation, and these ylides were also found to be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…Prior to this work (22) , it was found that fused pyrrolidines had been prepared by the 1,3-anionic cycloaddition of a series of Schiff bases to 1,4-benzoquinone and the reaction was controlled by the type of the substituent on the Schiff base and it was found that electron-donating groups need less energy to afford the final product compared with the electron-withdrawing groups. In the present work it is found that both -arylidene cyclohexanones (1)(2)(3)(4) and Schiff bases (5-10) control the rate of the reaction and H.F (-97) Kcal/mole for dimethoxy derivatives is the lowest value compared with H.F (50.561 and 50.563) Kcal/mole for the nitro derivative and the chlorobromo derivative respectively, which means that electron-donation enhances the rate and electron-withdrawal inhibits the rate of the reaction.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Prior to this work (22) , it was found that fused pyrrolidines had been prepared by the 1,3-anionic cycloaddition of a series of Schiff bases to 1,4-benzoquinone and the reaction was controlled by the type of the substituent on the Schiff base and it was found that electron-donating groups need less energy to afford the final product compared with the electron-withdrawing groups. In the present work it is found that both -arylidene cyclohexanones (1)(2)(3)(4) and Schiff bases (5-10) control the rate of the reaction and H.F (-97) Kcal/mole for dimethoxy derivatives is the lowest value compared with H.F (50.561 and 50.563) Kcal/mole for the nitro derivative and the chlorobromo derivative respectively, which means that electron-donation enhances the rate and electron-withdrawal inhibits the rate of the reaction.…”
Section: Resultssupporting
confidence: 50%
“…Claisen-Schimdt condensation had been used to afford the four arylidene cyclohexanones (1)(2)(3)(4) to be used as a starting materials to get the spiro products after their reaction with the synthesized N-arylidene benzylamines (5-10) through 1,3-anionic cycloaddition (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In various approaches to the assembly of the 5,11‐methanomorphanthridine skeleton, the five types of advanced synthons I – V (Scheme ) have been strategically involved,6–10 and the closure of ring C, D, C/D, or E has constituted the final step in the construction of the polycyclic system. Significantly, the synthetic elaboration of these synthons I – V has involved the elegant development and application of many novel methodologies (e.g., an aza‐Cope rearrangement/Mannich cyclization,5a, 6a an allenylsilane imino ene reaction,9b,c a [3+2] cycloaddition,6b,g, 10 and a chemoenzymatic approach6i,k,l). Despite the substantial progress made in the racemic5, 6c–e,o, 7, 8, 9a, 10 and asymmetric6a,b,fn, 9b,c synthesis of the montanine‐type alkaloids, a general strategy for the effective bioinspired total synthesis of these architecturally unique molecules has not previously been explored.…”
Section: Methodsmentioning
confidence: 99%
“…3 While nonstabilized 1 2-azaallyllithiums (i.e., those bearing only alkyl or hydrogen) are not available by the deprotonation technique, we found that tin-lithium exchange on (2-azaallyl)stannanes, 3, was useful for the generation of such anions for both inter-and intramolecular cycloadditions. 4,5 Despite these successes, we continue to explore other routes to 2-azaallyl anions, since deprotonation is limited to semi-stabilized-(or stabilized-) anion formation and tin-lithium exchange is subject to the usual undesirable attributes of tetraalkyltin chemistry. Herein we report studies on two alternative approaches to 2-azaallyllithium formation, namely the electrocyclic ring-opening of N-lithioaziridines, 4, and the 1,3-anionic cycloreversion of Nlithioimidazolidines, 5.…”
Section: Introductionmentioning
confidence: 99%